MONITORING OF LEGISLATION ON INTENTIONAL SELF-HARM (SELF-MUTILATION) - Kaliakperova Елена Николаевна; Yerkinkyzy Зарина (Scientific and legal journal «Bulletin of the Institute of Legislation and Legal Information of the Republic of Kazakhstan», 2024)
The authors examined the criminal law institution of intentional self-harm (self-mutilation). The Constitution of the Republic of Kazakhstan extends to the area related to the legal status of the individual, and applies in full to citizens of the state deprived of liberty and placed in penitentiary institutions. They are limited to a certain extent of rights and freedoms, but these restrictions should not contradict the Constitution of the Republic of Kazakhstan. The study examined foreign experience of the institution of deliberately causing any damage to oneself (self-mutilation), as well as international legal acts recognized by the Republic of Kazakhstan and other states of the modern world. Is an act of self-harm committed by a convicted person one of the ways to protect his rights to freedom of speech and expression, a form of protest against the illegal actions of the administration of the institution, or a criminal offense? Criminal liability with the participation of a group of persons in this act is also considered. A legal analysis of Article 428 of the Criminal Code of the Republic of Kazakhstan and Article 130 of the Criminal Executive Code of the Republic of Kazakhstan was carried out, which indicate certain shortcomings in the presentation that create conditions for ambiguous understanding and application. It is possible to bring to criminal liability for participation in group disobedience, involving the deliberate infliction of any harm on oneself, if the purpose of self-harm is ignoring the legal requirements of the administration of the institution and violating the established procedure for serving a sentence. All these issues were considered by the authors in this article.